Improving Human Capital through Better Education to Support Indonesia’s Economic Development - Latif Adam; Siwage Dharma Negara (Institute for Economic and Social Research, 2015)
AbstractDespite Indonesia’s impressive economic growth, it still lags behind other countries with a similar income level in terms of the quality of its human capital. This paper argues that one key factor explaining this low quality of human capital relates to the lack of focus and clear strategies to develop its education system. This paper attempts to assess Indonesia’s current state of human capital development with particular focus on its education sector. In order to benefit from its demographic bonus, Indonesia needs to to improve its current education and skill training system. Better education and skill training system will support the country’s effort to reduce poverty and youth unemployment. The effectiveness of public spending in education should be improved to raise the quality of education. Indonesia needs to integrate its human capital development plan with its economic master plan.Keywords: Human Capital; Poverty; Unemployment; Education; DevelopmentAbstrakMeskipun mencatatkan pertumbuhan ekonomi yang mengagumkan, kualitas sumber daya manusia Indonesia masih tertinggal dibandingkan negara lain dengan tingkat penghasilan setara. Tulisan ini berpendapat bahwa faktor kunci yang menjelaskan rendahnya kualitas sumber daya manusia berhubungan dengan ketiadaan strategi yang terfokus dan jelas untuk mengembangkan sistem pendidikan Indonesia. Tulisan ini menilai kondisi kekinian dari pengembangan sumber daya manusia Indonesia dengan fokus khusus pada sektor pendidikan. Agar dapat mengoptimalkan manfaat dari bonus demografi, Indonesia perlu membenahi sistem pendidikan dan pelatihan keterampilan. Sistem pendidikan dan pelatihan keterampilan yang lebih baik akan menunjang upaya pengentasan kemiskinan dan pengurangan pengangguran muda. Efektivitas pengeluaran pemerintah di sektor pendidikan perlu ditingkatkan guna meningkatkan kualitas pendidikan. Indonesia perlu mengintegrasikan rencana pembangunan sumber daya manusia dengan master plan perekonomian.Kata kunci: Sumber Daya Manusia; Kemiskinan; Pengangguran; Pendidikan; PembangunanJEL classifications: I25; O15